Quantification of Cytoskeletal Dynamics in Time‐Lapse Recordings. Issue 2 (15th May 2019) - Schneider, René; Sampathkumar, Arun; Persson, Staffan
Abstract: The cytoskeleton is key to many essential processes in a plant cell, e.g., growth, division, and defense. Contrary to what "skeleton" implies, the cytoskeleton is highly dynamic, and is able to re‐organize itself continuously. The advent of live‐cell microscopy and the development of genetically encoded fluorophores enabled detailed observation of the organization and dynamics of the cytoskeleton. Despite the biological importance of the cytoskeletal dynamics, quantitative analyses remain laborious endeavors that only a handful of research teams regularly conduct. With this protocol, we provide a standardized step‐by‐step guide to analyze the dynamics of microtubules. We provide example data and code for post‐processing in Fiji that enables researchers to modify and adapt the routine to their needs. More such tools are needed to quantitatively assess the cytoskeleton and thus to better understand cell biology. © 2019 by John Wiley & Sons, Inc.